2004
DOI: 10.1017/s0950268804002973
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C in drug users in Flanders: determinants and geographic differences

Abstract: SUMMARYThe prevalence of hepatitis C and related risk factors in drug users were compared in two geographic regions in Belgium, the city of Antwerp and the mixed urban-rural area of Limburg. All 310 participants were surveyed and screened for hepatitis B, hepatitis C and HIV. Prevalence rates of anti-HCV, anti-HBc and anti-HIV were 71, 62 and 4% in Antwerp and 46, 21 and 0% in Limburg respectively. Injecting drug use, duration of injecting drug use, work as a commercial sex-worker, originating from Turkey or N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 89%
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 89%
“…Among the 310 drug users in Antwerp, prevalence of anti-HCV antibody was 71% and in Limburg in Belgium was 46% (Matheï et al, 2005). The Hepatitis C European Network for C-operative Research (HENCORE) group had reported the prevalence of 80% hepatitis C among intravenous drug users (IVDU) (Touzet et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, intravenous drug abuse has become the main cause of HCV transmission in developed areas such as Europe and the USA [9,10] . The estimated prevalence of HCV infection among injecting drug users (IDUs) is between 30 and 80% [11][12][13] . The number of IDUs in Japan is steadily increasing, particularly among young people, according to the data published by the Ministry of Health, Labour and Welfare.…”
Section: Features Of Recent Hcv Transmission In Japanmentioning
confidence: 99%